Band Overdrive: A Multi-Instrument Virtual Reality Music Rhythm Game - Wang, Junjie; Liao, Shuqi; Wang, Hao; Mousas, Christos (2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2022)
Music rhythm games have a tremendous audience in the modern game industry. However, most of these games have been deployed for mobile devices, desktop computers, or game consoles. Although users can still experience the excitement of playing music by tapping on-screen buttons or using controllers, the user experience still has more room for improvement. We therefore developed a network-based multiuser virtual reality music rhythm game in which users can choose their preferred instrument or sing as a band while also collecting points based on their performance.